2018
DOI: 10.1016/j.ejvs.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

One Year Outcomes of 101 BeGraft Stent Grafts used as Bridging Stents in Fenestrated Endovascular Repairs

Abstract: BeGraft stent grafts used as bridging stents during FEVAR are associated with favourable outcomes at 1 year follow-up. Long-term follow-up is required to confirm these promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…Although the clinical impact of this finding cannot be derived from the present study, it seems to correspond to the reported recently favorable early outcomes of the second-generation BeGs used as renal artery BSGs. 1 Moreover, the present study showed also a significant impact of the type of main device on the geometrical changes of the BSGs after fEVAR with larger L1/L2 ratios in the Zenith stent-graft vs the Anaconda. The most probable explanation is the greater stiffness of the Zenith owing to its Z-stent design compared to the ring stent and unsupported main body design of the Anaconda.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although the clinical impact of this finding cannot be derived from the present study, it seems to correspond to the reported recently favorable early outcomes of the second-generation BeGs used as renal artery BSGs. 1 Moreover, the present study showed also a significant impact of the type of main device on the geometrical changes of the BSGs after fEVAR with larger L1/L2 ratios in the Zenith stent-graft vs the Anaconda. The most probable explanation is the greater stiffness of the Zenith owing to its Z-stent design compared to the ring stent and unsupported main body design of the Anaconda.…”
Section: Discussionsupporting
confidence: 60%
“…Today, there are 3 other balloon-expandable covered stents that have also been used as bridging stent-grafts (BSGs) in fEVAR procedures: the BeGraft (BeG; Bentley InnoMed, Hechingen, Germany), introduced in 2013, the LifeStream (BD/Bard, Tempe, AZ, USA), introduced in 2014, and the balloon-expandable Viabahn VBX (Gore Medical, Flagstaff, AZ, USA), introduced in 2018. Favorable outcomes with 99% TV patency after 1 year have been reported for the second-generation BeG stent-grafts in fEVAR, 1 and a recent in vitro study has confirmed their superior properties compared with the first-generation BeG. 2 Recently, the first positive results were also published about the Viabahn VBX used in fEVAR and branched EVAR (bEVAR).…”
Section: Introductionmentioning
confidence: 99%
“…13,16,19,20) The single-centre prospective study series report 1-year outcomes of 101 BeGraft stent grafts used as bridging stents during FEVAR as a 98% patency rate. 21) Analysing the literature is difficult as a mix of complex abdominal AAA and thoraco-abdominal aneurysm are reported. 21)…”
Section: Discussionmentioning
confidence: 99%
“…21) Analysing the literature is difficult as a mix of complex abdominal AAA and thoraco-abdominal aneurysm are reported. 21)…”
Section: Discussionmentioning
confidence: 99%
“…Stephan Haulon's group reports early results using a new bridging stent to seal target side branch vessels during custom fenestrated stent repair. 1 The latest generation of the BeGraft stent has been modified by doubling the thickness of the expanded polytetrafluoroethylene covering used in the first generation device. It differs from other commonly used stents by being made of cobalt chromium rather than stainless steel and is available in a greater range of length and diameter combinations.…”
mentioning
confidence: 99%